7th International Conference on Higher Education Advances (HEAd'21) 2021
DOI: 10.4995/head21.2021.12603
|View full text |Cite
|
Sign up to set email alerts
|

Students' self-perceptions of mindfulness after learning mindfulness techniques in a professional skills course

Abstract: In this paper we describe the effect of incorporating two mindfulness techniques (keeping a diary and motivational interviewing) in a professional skills course, and the impact these had on students’ self-perceptions of mindfulness. Over the course of a fourteen-week semester, students were asked to keep a diary at four different time points and were also taught motivational interviewing skills, which they had to apply to a four-part counseling project. Using a pre-post study design and the validated tool, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Regarding the effect of the MMI intervention on cognitive health, the most important finding was the significant increase in mindfulness scores among the intervention group participants. This effect is consistent with the results reported in a study that showed a positive effect of MI on university students' mindfulness 18 . The follow‐up analyses also showed a significant between‐subjects mean difference in the scores of cognitive fusion and impulsivity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding the effect of the MMI intervention on cognitive health, the most important finding was the significant increase in mindfulness scores among the intervention group participants. This effect is consistent with the results reported in a study that showed a positive effect of MI on university students' mindfulness 18 . The follow‐up analyses also showed a significant between‐subjects mean difference in the scores of cognitive fusion and impulsivity.…”
Section: Discussionsupporting
confidence: 91%
“…This effect is consistent with the results reported in a study that showed a positive effect of MI on university students' mindfulness. 18 The follow-up analyses also showed a significant betweensubjects mean difference in the scores of cognitive fusion and impulsivity. The MMI intervention participants had lower impulsivity and higher cognitive fusion than the control group participants.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation